BRAZILIAN SIGN LANGUAGE (LIBRAS) AS A MANDATORY CURRICULAR COMPONENT: A LOOK AT THE CHEMISTRY UNDERGRADUATE COURSES ON THE THREE STATE UNIVERSITIES IN SAO PAULO - Maltoni, Naira Biagini [UNESP]; Torres, Julio Cesar [UNESP]; Santos, Thalita Alves dos (Unesp-faculdade Ciencias & Letras, 2021)
The 5626/2005 Decree establishes Brazilian Sign Language (LIBRAS) as a mandatory curricular component in the Undergraduate Teaching Degree and Speech-Language Pathology courses. This work aims to understand how the three state Universities in Sao Paulo offer these subjects in Chemistry undergraduate courses. A total of eight courses were analyzed, since, except for Unicamp (University of Campinas), both USP (Sao Paulo University) and UNESP (Sao Paulo State University) present this modality on more than one campus. To collect the data, an online survey was carried out on the websites of the universities on the portal of the aforementioned courses, in which class schedules and the Pedagogical Political Project were consulted. To discuss the data, the Bereday method was chosen, going through the stages of definition, interpretation, juxtaposition, and comparison. As the Decree does not establish rules, the research was able to expose how each university developed the discipline and discuss weaknesses and strengths of the chosen methods.
Keywords: Chemistry undergraduate courses; Brazilian Sign Language (LIBRAS); Comparative education; Public policies